S73 Viruses associated with community-acquired pneumonia in children – a large prospective study in the post-prevenar 13 era. (15th November 2016) - Wort, AS; Gale, M; Devine, K; Simpson, AJ; Sails, AD; Spencer, DA; Thomas, MF; Brodlie, M
Abstract : Introduction and objectives: Community-acquired pneumonia (CAP) is a common childhood illness and frequent reason for hospital admission. CAP may be caused by bacteria or viruses. Many studies have relied on administrative records that typically provide poor quality retrospective aetiological data. We have performed a large prospective study to investigate the aetiology of CAP in the 'post-Prevenar 13 era'. We wished to describe the current epidemiology of viral CAP and compare this with data from studies that used similar methodology in the same population in 2009–2011 (post-Prevenar 7) and 2001–2002 (pre-Prevenar 7). Methods: Children aged under 16 years admitted to a large paediatric centre, between January 2015 and June 2016, with a chest radiograph meeting WHO criteria were eligible. Following informed consent nasopharyngeal aspirate, nasal swab, sputum or endotracheal secretions were collected. Influenza A and B, Human Rhinovirus, Human Metapneumovirus, Adenovirus, Parainfluenza 1 – 4 and Respiratory Syncytial Virus (RSV) were tested using real-time PCR assays. Comparisons were made using appropriate non-parametric tests. Results: A total of 148 children were recruited, median age 2.7 years, IQR 1.5–5.3. Samples from 63 participants (43%) were positive for a virus and 7 cases had co-infection with 2 viruses. Children that tested positive for a virus were significantly younger (median 2.1 years, IQR 1.2–3.2, versus 3.7 years, IQR 1.9–6.9, p = 0.0005). When compared with previous studies there was no significant change in the virus detection rate. The breakdown of individual viruses is shown in the table, no significant changes were identified apart from a reduction in RSV. Conclusions: These results represent the most comprehensive data available on viruses associated with CAP in children in the UK in the 'post-Prevenar 13 era'. They confirm that there has not been a significant shift in the viruses associated with children requiring admission to hospital. Our results also suggest that the introduction of the live attenuated intranasal influenza vaccine to children, which began in 2013, is yet to have a significant effect on the frequency of influenza detected in children with CAP. Future surveys will be important for ongoing evaluation of the viral aetiology of CAP. Reference: Elemraid MA, et al . Aetiology of paediatric pneumonia after the introduction of pneumococcal conjugate vaccine. Eur Respir J 2013;42 (6):1595–603.